2017
DOI: 10.4238/gmr16019173
|View full text |Cite
|
Sign up to set email alerts
|

A study on natural recovery of tassel fertilization and doubling method in maize haploids

Abstract: ABSTRACT. Doubling method is the technical barriers in maize haploid breeding. It was very important to establish the independent intellectual property rights for doubling method. In this experiment, the maize haploid inducer, TG15, was used for producing maternal haploids. Also, haploids were obtained from two kinds of maternal genotypes involved in the experiment, including high-oil type and common type. Significant differences were observed among offspring of various genotypes in the recovery of haploid fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…On average, a colchicine treatment survival was 85.7% for all populations (Table 3). Lower seedling survival rates were observed in other studies, commonly amounting to 60-70% on average (Dang et al, 2012;Battistelli et al, 2013;Jiang et al, 2017).…”
Section: Resultscontrasting
confidence: 52%
“…On average, a colchicine treatment survival was 85.7% for all populations (Table 3). Lower seedling survival rates were observed in other studies, commonly amounting to 60-70% on average (Dang et al, 2012;Battistelli et al, 2013;Jiang et al, 2017).…”
Section: Resultscontrasting
confidence: 52%
“…Recent studies reported that HMF is genotype dependent (Wu et al 2016;Ma et al 2018). In Chinese germplasm, Jiang et al (2017) found minimal levels of HMF from 4% to 11% with an average of 8.28%.…”
Section: Introductionmentioning
confidence: 97%
“…Generally, haploids are sterile, while fertile gametes could be produced when the chromosomes are doubled. Most of the current chromosome doubling methods depend on antimitotic chemical reagents, such as colchicine, amiprophos-methyl (APM) and pronamide [ 11 , 12 , 13 , 14 ]. Traditionally, colchicine treatment of haploids results in a better doubling effect.…”
Section: Introductionmentioning
confidence: 99%